Transforming the paradigm of child welfare. (May 2021) - Cerulli, Catherine; Cicchetti, Dante; Handley, Elizabeth D.; Manly, Jody Todd; Rogosch, Fred A.; Toth, Sheree L.
Abstract: As a founder of the field of applied developmental psychology, Dr Edward Zigler promoted public policy that translated scientific knowledge into real-world programs to improve the outcomes of high-risk children and families. Many researchers, practitioners, and public policy proponents have sought to carry on his legacy through integration of empirical research, evidence-based prevention and intervention, and advocacy to address a range of challenges facing families with young children. To advance the field of child maltreatment, a multidisciplinary team of investigators from the Universities of Rochester and Minnesota partnered with the Eunice Kennedy Shriver National Institute of Child Health and Human Development to create the T ranslational R esearch that A dapts N ew S cience FOR M altreatment Prevention Center (Transform). Building on state-of-the-art research methodologies and clinical practices, Transform leverages theoretically grounded research and evidence-based interventions to optimize outcomes for individuals across the life span who have experienced, or may be at risk for, maltreatment. Inspired by the work of Dr Zigler, Transform is committed to bridging science and real-world practice. Therefore, in addition to creating new science, Transform's Community Engagement Core provides translational science to a broad audience of investigators, child-serving professionals, and parental and governmental stakeholders. This article describes Transform's purpose, theoretical framework, current activities, and future directions.